Lung fibrosis in sarcoidosis. Is there a place for antifibrotics? - Bączek, Karol; Piotrowski, Wojciech Jerzy (Frontiers in Pharmacology, 2024)
Sarcoidosis, an enigmatic disease with unknown etiology, is characterized by inflammation and the potential involvement of various organs, predominantly the lungs and intrathoracic lymph nodes. Non-caseating granulomas can resolve spontaneously in approximately 60% of cases within 2–3 years. However, sarcoidosis-related mortality has increased. Lung fibrosis, affecting up to 20% of sarcoidosis patients, stands out as a primary cause of mortality. Traditionally, fibrosis is viewed because of prolonged inflammation, necessitating anti-inflammatory treatment with systemic steroids, immunosuppressants, and anti-TNF agents to manage the disease. The recent introduction of antifibrotic drugs such as nintedanib and pirfenidone offers new avenues for treating fibrotic sarcoidosis. Nintedanib, effective in idiopathic pulmonary fibrosis (IPF) and systemic sclerosis-related interstitial lung disease (SSc-ILD), has shown promise in patients with various progressive fibrosing interstitial lung diseases (PF-ILD), including those with sarcoidosis. Pirfenidone, also effective in IPF, has demonstrated potential in managing fibrotic sarcoidosis, though results have been inconclusive due to limited participant numbers in studies. This review explores the theoretical and empirical evidence supporting the use of antifibrotics in sarcoidosis, weighing the benefits and drawbacks. While antifibrotics offer a potential therapeutic approach, further randomized controlled trials are essential to determine their efficacy in fibrotic sarcoidosis. Addressing fibrosis as a continuum of chronic inflammation, the role of antifibrotics in managing sarcoidosis remains an area requiring more in-depth research to improve patient outcomes and advance treatment paradigms.